Diamela Eltit Essays on Chilean Literature, Politics, and Culture - Lazzara, Michael J.; Barrientos Olivares, Mónica; Olivera-Williams, Rosa (Latin America Research Commons, 2023)
Diamela Eltit's literary work emerged on the Chilean cultural scene in the 1980s when the Pinochet regime (1973-1990) had consolidated its project of extermination, censorship, and neoliberal shock therapy. Forced to write in a suffocating atmosphere of restriction and violence, Eltit boldly cultivated a radical, insurrectional poetics aimed at questioning the very underpinnings of authoritarian power and discourse. While Eltit's novels, published between 1983 and the present, provide a remarkable vision of Chile that has evolved over the past decades, she offers a different vantage point through her prolific and rigorous cultivation of literary essays. Translated for the first time into English, this collection of Eltit's essays allows readers to delve into her key concerns as a writer and intellectual: the neoliberal marketplace; the marginalization of bodies in society; questions of gender and power; struggles for memory, truth, and justice after dictatorship; and the ever-complex relationships among politics, ethics, and aesthetics.